Analyse de l’évolution spatiotemporelle de la tendance des extrêmes chauds au Sénégal - Moussa Sow; Demba Gaye; Mouhamadou Mawloud Diakhate (VertigO, 2024)
Climate variability manifests itself, among other things, through climatic phenomena such as droughts, heatwaves, floods, rainfall delays and heat waves. The latter are expected to be longer, more frequent and more intense on the African continent and in the Sahel in particular. In this context, it seems important to conduct studies on these phenomena, particularly at national level, to gain a better understanding of the potential impact on populations. This research therefore analyses the spatiotemporal changes and trends in hot extremes (95th percentile of Tmax and Tmin) in Senegal over the period 1 984-2020. To achieve this objective, the spatiotemporal distribution of averages of warm extremes (95th percentile of Tmax and Tmin) over the period was first determined, followed by the determination of anomalies in the 95th percentile of Tmin and Tmax using Lamb's test. The Pettitt test was then used to identify the break years, and finally the Mann Kendall test was used to identify trends in the 95th percentile of Tmin and Tmax for the period 1984-2020. The data are gridded spatial climate reanalyses with a spatial resolution of 0.5° * 0.625°. The results obtained show an increase in the 95th percentile Tmax and Tmin for all the stations in the study. On a national scale, this increase is estimated at +0.38°C for the 95th percentile Tmax and +0.50°C for the Tmin. This shows that the 95th percentile of Tmins is rising faster than Tmaxes, and that this trend is significant at almost all of the 40 stations in the study. As a follow-up to this work, it would be important to analyse the characteristics of heat waves in Senegal.